Le Paysage. Une médiation héritée entre l’homme et la nature face à l’écologisation contemporaine des sensibilités esthétiques - Serge Briffaud (Projets de Paysage)
This article shows how the desire to promote an ecologised aesthetic relationship with the environment, something which has emerged in recent decades through the philosophical movement of environmental aesthetics, raises the question of the historical role of the landscape as a mediator between Humankind and Nature. The first part presents the critical review of the theorists of this movement which considers the perception of nature through the landscape and the inherited codes guiding such a perception. It then examines the cognivitist theories in environmental aesthetics, insofar as the latter proposes a remediation of aesthetic appreciation via scientific ecology and related sciences. The third part places these theories in a long history of the aesthetics of nature and the landscape, showing how they relate to some of the major founding principles of neoclassical art. The article concludes with a counterproposal, consisting of the construction of a mediation of the landscape between societies and the socio-ecological complexity of environments.